Does Adjuvant Steroid Therapy Post-Kasai Portoenterostomy Improve the Outcome of Biliary Atresia? A Systematic Review and Meta-Analysis. (2011) - Sarkhy, Ahmed; Schreiber, Richard A; Milner, Ruth; Barker, Collin C
Abstract : BACKGROUND: The role of adjuvant steroid therapy in the postoperative management of patients with biliary atresia (BA) is unclear. OBJECTIVE: To systematically review the literature and perform a meta-analysis to determine the efficacy of adjuvant steroid therapy post-Kasai portoenterostomy (KP) on BA outcome. METHODS: A systematic review and meta-analysis of randomized trials and/or observational studies that examined the role of steroids on BA outcomes published between January 1969 and June 2010 was conducted. Studies were identified using the Medline, PubMed, EMBASE and Cochrane databases. RESULTS: Sixteen observational studies and one randomized controlled trial (RCT) were found. Four of the 16 observational studies (160 participants) and the RCT (73 participants) met the entry criteria and were eligible to be included in the analysis. There was no statistically significant difference in the effect of steroids either on normalizing serum bilirubin levels at six months (pooled OR 1.48 [95% CI 0.67 to 3.28]) or in delaying the need for early liver transplantation (within the first year post-KP (pooled OR 0.59 [95% CI 0.21 to 1.72]). CONCLUSION: The present meta-analysis did not find a significant effect of steroid over standard therapy, either in normalizing serum bilirubin levels at six months or at delaying the need for early liver transplantation post-KP. RCT studies of sufficient size and comprehensive design using high-dose steroids are needed to determine the effectiveness of steroids on the short and intermediate post-KP outcomes for BA patients.